فاعلية نشاط التعبئة والتغليف للمنتجات: دراسة تحليلية لعبوات مصنع البان تكريت - د. جرجيس عمير عباس; انيس احمد عبد الله; د. حكمت رشيد (PROSPECTIVE RESEARCHES, 2023)
The research showed the fact that the activity of packing in Tikret dairy product has been negligent, especially if we consider the standards for packing those kinds of products, which are: practical, visual, informational, and reactiveness criteria. Most consideration was put on sides rather than what the customers desire. The studied showed also that the consumers look for new shapes and modern packing, as well as, new products. These desires will be of great benefits for both the factory and the consumers themselves.